2020
DOI: 10.1186/s41747-020-00194-x
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical analysis of skull trauma and opportunity in neuroradiology interpretation to explain the post-concussion syndrome: literature review and case studies presentation

Abstract: Traumatic head injuries are one of the leading causes of emergency worldwide due to their frequency and associated morbidity. The circumstances of their onset are often sports activities or road accidents. Numerous studies analysed post-concussion syndrome from a psychiatric and metabolic point of view after a mild head trauma. The aim was to help understand how the skull can suffer a mechanical deformation during a mild cranial trauma, and if it can explain the occurrence of some post-concussion symptoms. A m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In the Greek population examined by Chovalopaulou et al, the highest FA was found in the skull-base region [9]. The clinical importance of asymmetry of jugular foramen was suggested by Distriquin et al in their paper in which they indicated a direct relation between the posttraumatic asymmetry of skull-base foramina and symptoms of the post-concussion syndrome [13].…”
Section: Skull Symmetrymentioning
confidence: 93%
“…In the Greek population examined by Chovalopaulou et al, the highest FA was found in the skull-base region [9]. The clinical importance of asymmetry of jugular foramen was suggested by Distriquin et al in their paper in which they indicated a direct relation between the posttraumatic asymmetry of skull-base foramina and symptoms of the post-concussion syndrome [13].…”
Section: Skull Symmetrymentioning
confidence: 93%
“… 55 , 56 A recent systematic review of clinical evidence concluded that the cranium can be deformed even by an mTBI. 57 Further, several case studies suggest that damage proximal to the cranial base in particular can contribute to neurovascular dysfunction, which may underlie some of the acute symptoms associated with concussion, such as dizziness and headache. 57 …”
Section: Mild Traumatic Brain Injuries Alter the Calvarial Bone And U...mentioning
confidence: 99%